Comprehensive Assessment of Plasma Circ_0004771 as a Novel Diagnostic and Dynamic Monitoring Biomarker in Gastric Cancer - Xu, Yanhua (Onco Targets Ther, 2020)
PURPOSE: Due to the lack of specific and sensitive detection indicators, most patients with GC are already in the advanced stage at the time of diagnosis. Therefore, it is urgent to search for effective diagnostic biomarkers that can be applied in clinic. MATERIALS AND METHODS: We screened out circ_0004771 through circRNA sequencing. Exonuclease digestion assay, agarose gel electrophoresis (AGE) and Sanger sequencing verified the potential of circ_0004771 being a biomarker. Additionally, we established quantitative real-time fluorescent polymerase chain reaction (qRT-PCR) to detect the expression level of circ_0004771 and evaluated the methodology. What's more, we collected plasma samples from 120 GC patients, 40 superficial gastritis patients, 20 postoperative GC patients, 20 postoperative recurrence patients and 120 healthy donors. We constructed the receiver operating characteristic curve (ROC) to appraise its diagnostic efficacy. RESULTS: The expression level of circ_0004771 is up-regulated in GC tissues, which is consistent with circRNA sequencing result (P=0.0001). Circ_0004771 can serve as a promising biomarker because of its stable structure and longer half-life. Plasma circ_0004771 expression is markedly richer in GC patients than that in normal people (P<0.0001), and the area under the ROC (AUC) is 0.831 (95% CI: 0.779–0.883). The diagnostic efficacy of circ_0004771 is higher than that of CEA (AUC=0.747, 95% CI: 0.686–0.808) and CA199 (AUC=0.508, 95% CI: 0.433–0.583). Higher diagnostic efficacy can be achieved by combination diagnosis for distinguishing GC patients from normal people (AUC=0.864). Besides, the expression level of circ_0004771 can distinguish GC patients from gastritis patients (AUC=0.845, 95% CI: 0.772–0.917). The plasma circ_0004771 expression in GC patients decreased to normal after surgery (P<0.0001). In addition, plasma circ_0004771 expression increased again in patients with postoperative recurrence. CONCLUSION: Plasma circ_0004771 is differentially expressed in GC patients, postoperative GC patients and patients with recurrence, suggesting that plasma circ_0004771 can be used as a novel diagnostic and dynamic monitoring biomarker in GC.